Cross-country skiers often experience respiratory symptoms during and after exercise but have a low prevalence of prolonged cough - Jari Parkkari; Maarit Valtonen; Jussi Karjalainen; Lauri Lehtimäki; Heini Huhtala; Heikki Koskela; Rikhard Mäki-Heikkilä (BMJ Open Sport & Exercise Medicine, 2023)
Background Cross-country skiers train and compete during the winter for long periods of time in subfreezing conditions, which strains the airways and provokes respiratory symptoms. This study aimed to compare the prevalence of exercise-related symptoms and prolonged cough in competitive cross-country skiers versus the general population and to investigate the association between these symptoms and asthma.Methods A questionnaire was sent to Finnish cross-country skiers (n=1282) and a random sample of the general population (n=1754), with response rates of 26.9% and 19.0%, respectively.Results Both groups were mostly asymptomatic at rest, but symptoms were increased in both groups during and after exercise. Cough was more prevalent after exercise in skiers and phlegm production was more common during and after exercise in skiers. Asthma did not provoke specific symptoms, but symptom prevalence was higher in asthmatic individuals. Skiers had a higher prevalence of cough after exercise (60.6% vs 22.8%, p<0.001) compared with controls, but controls had a higher prevalence of prolonged cough (4.1% vs 9.6%, p=0.004). In participants without asthma, cold air triggered symptoms more often in skiers than controls, while strong odours triggered symptoms more often in asthmatic controls than skiers. Chronic cough lasting more than 8 weeks was rare, reported by 4.8% of controls and 2.0% of skiers.Conclusion Cross-country skiers, especially those with asthma, experience a higher burden of exercise-related respiratory symptoms compared with controls. However, repeated exposure to cold air does not appear to result in long-term hypersensitivity of the cough reflex arc.